ACCIDENTS AND EMERGENCIES - Qo’ldosheva Mo’tabar Muhtarovna (TADQIQOTLAR, 2026)
Accident - a case of bodily injury, disability or death as a result of various natural disasters,  accidents  and  other  unfortunate  events.  The  laws  of  the  Republic  of Uzbekistan establish appropriate penalties for persons who have caused accidents by violating safety rules at enterprises, construction, transport, mines and other places. In particular, the Criminal Code of the Republic of Uzbekistan provides for appropriate penalties for violations of the rules for the use of radioactive materials and nuclear installations, their unauthorized use, violations of safety, labor protection, fire safety rules during research work, mining, construction or blasting operations, and crimes committed in violation of the safety of transport traffic and the use of vehicles.